Creating Two Book Manuscripts. - Bynum, Terrell (2001)
Keywords: dept.phi; faculty_collection; sabbatical_report

Ethics and Information Technology: Guest editor's introduction - Bynum, T.W. (Ethics and Information Technology, 2001)
Keywords: Information technology; Social sciences; dept.phi

Computer ethics: Its birth and its future - Bynum, Terrell Ward (Ethics and Information Technology, 2001)
This article discusses some "historical milestones" in computer ethics, as well as two alternative visions of the future of computer ethics. Topics include the impressive foundation for computer ethics laid down by Norbert Wiener in the 1940s and early 1950s; the pioneering efforts of Donn Parker, Joseph Weizenbaum and Walter Maner in the 1970s; Krystyna Gorniak's hypothesis that computer ethics will evolve into "global ethics"; and Deborah Johnson's speculation that computer ethics may someday "disappear"., (C)2001 Kluwer Academic Publishers
Keywords: Applied ethics; Computer ethics; Cybernetics; Global ethics; Information ethics; Information technology; Philosophical aspects; Professional responsibilities; Professional responsibility; Social sciences; applied ethics; computer ethics; cybernetics; dept.phi; global ethics; information ethics; professional responsibility; ❓ Multiple DOI

The challenge of applying ethics. - Bynum, Terrell Ward (Science and Engineering Ethics, 2001)
Keywords: *Computers; *Ethics; Computers; Ethics; Humans; article; computer; dept.phi; ethics; human

Revolution and the library - Gorniak-Kocikowska, K (Library Trends, 2001)
The focus of this article is primarily on the impact that the computer revolution has on college/university libraries, although many of the issues discussed here are relevant to other types of libraries as well. The university library in its present form is a product of the printing press revolution. In all likelihood, the computer revolution will have an even more profound impact on the library than did the printing press revolution.
Keywords: dept.phi; ⛔ No DOI found